Secure E-voting System by Utilizing Homomorphic Properties of the Encryption Algorithm - Rifki Suwandi; Surya Michrandi Nasution; Fairuz Azmi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The use of cryptography in the e-voting system to secure data is a must to ensure the authenticity of the data. In contrast to common encryption algorithms, homomorphic encryption algorithms had unique properties that can perform mathematical operations against ciphertext. This paper proposed the use of the Paillier and Okamoto-Uchiyama algorithms as two homomorphic encryption algorithms that have the additional properties so that it can calculate the results of voting data that has been encrypted without having to be decrypted first. The main purpose is to avoid manipulation and data falsification during vote tallying process by comparing the advantages and disadvantages of each algorithm.